(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
By examining the historic settlement of the Balochi people from West Asia to East Africa, this article seeks to study and examine their past immigration patterns, presence and current socio-political situation as a minority Muslim population. The Balochi people are an Indo-European ethnic Sunni Muslim minority population located in a region currently shared and divided by modern Islamic republics of Iran in West Asia and Pakistan in South Asia. The Balochis have formed a significant part of the non-indigenous Muslim population in East Africa since the late 17th century. Yet, there is not much written on them as a distinct Sunni Muslim minority group originating from historic Iran (including parts of South Asia) to Africa. Being part of a larger project, this study will explore the chief reasons behind the immigration of the Balochis to the regions of East Africa and how did their presence affect the local population and vice versa. The hypothesis is that the Balochis were formerly welcomed by the indigenous and non-indigenous population of East Africa and established amicable relationships with them. Using the method of qualitative content analysis combined with historical analysis, this article highlights the reciprocal impacts of the Balochi immigrants and indigenous people of East Africa.